2008
DOI: 10.1074/jbc.m801182200
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of Nitroglycerin by Purified Mitochondrial and Cytosolic Aldehyde Dehydrogenases

Abstract: Metabolism of nitroglycerin (GTN) to 1,2-glycerol dinitrate (GDN) and nitrite by mitochondrial aldehyde dehydrogenase (ALDH2) is essentially involved in GTN bioactivation resulting in cyclic GMP-mediated vascular relaxation. The link between nitrite formation and activation of soluble guanylate cyclase (sGC) is still unclear. To test the hypothesis that the ALDH2 reaction is sufficient for GTN bioactivation, we measured GTNinduced formation of cGMP by purified sGC in the presence of purified ALDH2 and used a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 38 publications
(45 reference statements)
7
76
0
1
Order By: Relevance
“…The inactivation of ALDH2 after each turnover was shown to be DTT-reversible, suggesting that it contributes to the development of nitrate tolerance. Although this mechanism may account for the main route of ALDH2-catalyzed GTN denitration, our recent work demonstrating an additional pathway yielding NO instead of nitrite (Beretta et al, 2008a) and partially DTT-irreversible inactivation of the enzyme by GTN (Beretta et al, 2008b) indicates that the reaction between ALDH2 and GTN may be more complex than originally assumed. In the present study, we mutated the cysteine residues adjacent to the catalytic nucleophile Cys302 and the putative general base Glu268 in human ALDH2 to clarify their function in GTN metabolism and GTN-induced enzyme inactivation.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The inactivation of ALDH2 after each turnover was shown to be DTT-reversible, suggesting that it contributes to the development of nitrate tolerance. Although this mechanism may account for the main route of ALDH2-catalyzed GTN denitration, our recent work demonstrating an additional pathway yielding NO instead of nitrite (Beretta et al, 2008a) and partially DTT-irreversible inactivation of the enzyme by GTN (Beretta et al, 2008b) indicates that the reaction between ALDH2 and GTN may be more complex than originally assumed. In the present study, we mutated the cysteine residues adjacent to the catalytic nucleophile Cys302 and the putative general base Glu268 in human ALDH2 to clarify their function in GTN metabolism and GTN-induced enzyme inactivation.…”
Section: Discussionmentioning
confidence: 76%
“…In 2002, Stamler and coworkers (Chen et al, 2002) showed that ALDH2 denitrates GTN to 1,2-glyceryl dinitrate (1,2-GDN) and nitrite and proposed that reduction of nitrite by components of the mitochondrial electron transfer chain could provide the link between ALDH2-catalyzed GTN metabolism and vasorelaxation. However, we found that 1) GTN activates sGC in the presence of purified ALDH2 , 2) ALDH2 catalyzes the reduction of GTN to NO, accounting for 5 to 10% of total GTN turnover (Beretta et al, 2008a;Wenzl et al, 2009), and 3) mitochondrial biotransformation of nitroglycerin is not affected by respiratory substrates or inhibitors (Kollau et al, 2009), suggesting that ALDH2 catalysis is sufficient for GTN bioactivation in blood vessels.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This enzyme catalyzes the formation of 1,2-glyceryl dinitrate (1,2-GDN) and inorganic nitrite from the metabolism of GTN, leading to the production of cGMP and vasorelaxation (3,10). Nitrite anion can be reduced to NO by enzymatic and nonenzymatic mechanisms, and it has been reported that vasodilator responses to GTN in the coronary and systemic vascular beds can be attenuated by cyanamide, an inhibitor of ALDH2 (3,8,45). However, the effects of cyanamide and allopurinol on responses to GTN have not been determined in the pulmonary vascular bed.…”
mentioning
confidence: 99%